722 IMPLEMENTATION OF TREATMENT ESCALATION PLANS IN A COMMUNITY PSYCHIATRIC HOSPITAL. (8th March 2022) - Chua, A Y T; Makh, S K; Ghanchi, A; Grayston, J; Yasmeen, N; Insigne, S M; Woolford, S; Wijayaweera, S; Patel, H P; Amin, J
Abstract: Introduction: Treatment Escalation Plans (TEP) detail appropriate ceilings of care and guide treatment of patients based on shared decision making. Whilst established in many acute trusts, TEP are not frequently used in community mental health hospitals. This is particularly concerning in organic mental health wards, where patients with severe dementia may be transferred to acute hospitals for treatment without consideration about whether this is appropriate. This quality improvement project aimed to develop and implement TEP within a community mental health hospital to support the management of our older patients with severe mental illness. Methods: We designed a TEP form based on a prototype used in a partner acute trust and evaluated its use on our wards, comprising 20 patients between August–September 2020. We obtained quantitative data on use of TEP, including the length of time from admission to completion, as well as qualitative data from healthcare staff regarding their experience of using TEP. Results: TEP implementation well received among members of staff. 100% of patients had a TEP in place within 2 weeks of admission. The mean time taken to complete a TEP was reduced from 7.1 days to 3.2 days following inclusion of the TEP proforma in admission packs. There was an improvement in understanding the purpose, comprehensiveness and location of TEP forms during their implementation. The key theme that arose from qualitative analysis of healthcare staff comments was that TEP forms provided clear guidance on appropriateness of escalation of care. Conclusion: TEP forms offer clear guidance to treating clinicians about the ceilings of care for patients. TEP were successfully implemented in our community mental health hospital and we plan further post-implementation evaluation. We intend to roll out the TEP form across our mental health trust and share findings nationally to promote best practice.